Systems Genetics Analysis of a Recombinant Inbred Mouse Cell Culture Panel Reveals Wnt Pathway Member Lrp6 as a Regulator of Adult Hippocampal Precursor Cell Proliferation. (21st March 2016) - Kannan, Suresh; Nicola, Zeina; Overall, Rupert W.; Ichwan, Muhammad; Ramírez-Rodríguez, Gerardo; N. Grzyb, Anna; Patone, Giannino; Saar, Kathrin; Hübner, Norbert; Kempermann, Gerd
Abstract: In much animal research, genetic variation is rather avoided than used as a powerful tool to identify key regulatory genes in complex phenotypes. Adult hippocampal neurogenesis is one such highly complex polygenic trait, for which the understanding of the molecular basis is fragmented and incomplete, and for which novel genetic approaches are needed. In this study, we aimed at marrying the power of the BXD panel, a mouse genetic reference population, with the flexibility of a cell culture model of adult neural precursor proliferation and differentiation. We established adult-derived hippocampal precursor cell cultures from 20 strains of the BXD panel, including the parental strains C57BL/6J and DBA/2J. The rates of cell proliferation and neuronal differentiation were measured, and transcriptional profiles were obtained from proliferating cultures. Together with the published genotypes of all lines, these data allowed a novel systems genetics analysis combining quantitative trait locus analysis with transcript expression correlation at a cellular level to identify genes linked with the differences in proliferation. In a proof-of-principle analysis, we identified Lrp6, the gene encoding the coreceptor to Frizzled in the Wnt pathway, as a potential negative regulator of precursor proliferation. Overexpression and siRNA silencing confirmed the regulatory role of Lrp6 . As well as adding to our knowledge of the pathway surrounding Wnt in adult hippocampal neurogenesis, this finding allows the new appreciation of a negative regulator within this system. In addition, the resource and associated methodology will allow the integration of regulatory mechanisms at a systems level.